Negative plate, lithium ion battery and electric equipment
By using the particle size combination of graphite, hard carbon and silicon-based materials in lithium-ion batteries, the volume expansion problem of silicon-based materials is solved, the energy density and cycling performance of the battery are improved, and the market demand for energy density and rate performance is met. .
Patent Information
- Application Number
- CN202411380243.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-09-30
AI Technical Summary
In existing lithium-ion batteries, the volume expansion of silicon-based materials during charging and discharging is severe, resulting in damage to the electrode conductive network and unable to meet the market's demand for energy density and rate performance.
The particle size of graphite, hard carbon and silicon-based materials is combined to increase the compaction density of the battery through the isotropy of hard carbon and wide layer spacing, limit the volume expansion of the silicon-based materials, and alleviate the interparticle through the hardness of the silicon-based materials. Locking problem improves the circulation and rate performance of the negative electrode sheet.
It effectively improves the energy density and circulation performance of lithium-ion batteries, improves the stability and rate performance of the battery, and meets the market's demand for fast charging.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to negative electrode sheets, lithium-ion batteries and electrical equipment. Background Art
[0002] Lithium-ion batteries have the advantages of high energy density, no memory effect, long cycle life, fast charge and discharge, and low self-discharge. They are widely used in consumer electronics, electric vehicles, energy storage and other fields. Among them, the choice of negative electrode active materials is directly related to the energy density of lithium-ion batteries, and also affects the rate performance. Thanks to the advantages of low lithium insertion potential, high theoretical specific capacity, price and environmental friendliness, graphite materials are currently the main choice for negative electrode active materials for lithium-ion batteries. However, as the market demand for the energy density and charging rate of lithium-ion batteries increases, graphite materials alone can no longer meet today's needs.
[0003] To this end, the usual method is to mix silicon-based materials into the negative electrode active material. The theoretical lithium storage capacity of silicon is as high as 4200mAh / g, and the lithium insertion platform is slightly higher than that of graphite. It has little safety hazard and is an excellent substitute for graphite-based negative electrode materials. However, silicon exhibits a volume change of up to 300% during charging and discharging, which can easily lead to pulverization of silicon particles and destruction of the conductive network inside the electrode. In addition, high-rate charging will lead to more obvious problems of lithium precipitation and silicon expansion, which cannot meet the market's fast charging needs. Therefore, how to more effectively alleviate the volume expansion of silicon particles, ensure the cycle stability of the battery, and obtain silicon-based negative electrode materials that take into account energy density, cycle performance, and rate performance is still a technical hotspot that needs to be urgently solved in the current lithium-ion battery field. Summary of the invention
[0004] The present application aims to solve at least one of the technical problems existing in the prior art. To this end, the present application proposes a negative electrode sheet, a lithium-ion battery and an electrical device.
[0005] In a first aspect of the present application, a negative electrode sheet is provided, the negative electrode sheet comprising a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector, the negative electrode active material layer comprising a negative electrode active material, and the negative electrode active material comprises a graphite material, a hard carbon material and a silicon-based material;
[0006] Among them, the particle size D50 of the graphite material, the particle size D′50 of the hard carbon material, and the particle size D″50 of the silicon-based material satisfy 1.5≤D50 / D′50≤2.5, 1.1≤D′50 / D″50≤3.
[0007] The negative electrode sheet according to the first aspect of the present application has the following beneficial effects:
[0008] Compared with graphite, hard carbon has a higher reversible capacity, which is beneficial to improve the energy density of lithium-ion batteries. It also has good isotropy, which can facilitate the insertion and extraction of lithium ions; but the compaction density of hard carbon cannot reach a very high level, which seriously affects the energy density of the battery. Silicon-based materials have higher specific capacity, which greatly improves the energy density of the battery, but there is a large volume expansion during the lithium insertion process. This solution effectively improves the shortcoming of low compaction density of hard carbon by matching the large and small particle sizes of graphite, hard carbon, and silicon-based materials, and improves the overall compaction density of the negative electrode, which is beneficial to the improvement of the energy density of the battery. Due to the good isotropy and wide interlayer spacing of hard carbon, it is beneficial to the infiltration of electrolyte, improves the liquid retention of the electrode, and also helps the rapid insertion of lithium ions and improves the rate performance. The small-particle silicon-based materials are distributed between the gaps between hard carbon and graphite, which can not only further improve the compaction density of the electrode, but also further limit the volume expansion during the lithium insertion process, thereby effectively improving the cycle performance of the battery.
[0009] In addition, since the hardness of silicon-based material particles is greater than that of hard carbon and graphite, they act as pulleys during the rolling process of the negative electrode sheet, which can alleviate the locking of hard carbon and graphite caused by their angular shapes, facilitate the slippage between particles, avoid local overpressure causing particle rupture, and maintain its cycle performance, rate performance and energy density.
[0010] In some embodiments of the present application, D50 is 10 to 17 μm, for example, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, or 17 μm.
[0011] In some embodiments of the present application, D′50 is 6 to 10 μm, for example, 6 μm, 7 μm, 8 μm, 9 μm, or 10 μm.
[0012] In some embodiments of the present application, D″50 is 3 to 7 μm, for example, 3 μm, 4 μm, 5 μm, 6 μm, or 7 μm.
[0013] In some embodiments of the present application, the defect degree I of the hard carbon material is 0.15 to 0.38; wherein I is the G peak area A when the hard carbon material is subjected to Raman spectroscopy testing. G and D peak area A D The D peak is at 1350cm -1 The characteristic peaks appearing near the carbon structure belong to the defective (disordered) carbon structure; the G peak is at 1580cm -1 The characteristic peaks appearing nearby belong to the ordered carbon structure.
[0014] The defect I of hard carbon materials characterizes the degree of graphitization of hard carbon materials. When the degree of graphitization of hard carbon materials is high, the lithium insertion of materials is more dependent on interlayer lithium storage, the specific surface area is low, and the pore structure is less, which cannot alleviate the volume expansion of materials during the cycle and easily leads to carbon layer peeling. When the degree of graphitization of hard carbon materials is low, the defect active sites become more, and the contribution to the capacity increases. The right amount of defects can improve the reversible capacity. At the same time, the isotropy is better, which is conducive to the adsorption of lithium storage, weakens the volume expansion in the thickness direction, and is conducive to maintaining the stability of the cycle. When the defect I of hard carbon is within the above range, the coordination and balance of the ordered structure and defect structure can be achieved, the reversible specific capacity and the first cycle coulomb efficiency are optimal, and the cycle performance and expansion rate of the battery are effectively improved.
[0015] In some embodiments of the present application, the Mohs hardness S1 of the graphite material is 0.8-2, the Mohs hardness S2 of the hard carbon material is 3-5, the Mohs hardness S3 of the silicon-based material is 5-7, and S2 <S3。
[0016] In some embodiments of the present application, the compaction density P, the porosity ε and the thickness H of the negative electrode active material layer of the negative electrode sheet satisfy Formula 1: 15≤(kε+H) / P≤39.05; in Formula 1: 1.26≤k≤1.40, P is expressed in g / cm 2 The unit is the dimensionless value for calculation, and the unit is μm for calculation. By adjusting the k value within a limited range and making the compaction density P, porosity ε, and active layer thickness H of the negative electrode sheet satisfy the relationship of formula 1, the negative electrode sheet can still have a good porosity at a high compaction density, which is conducive to the electrolyte infiltration of the electrode sheet and improves the diffusion efficiency of active ions.
[0017] In some embodiments of the present application, the compaction density P of the negative electrode sheet is 1.55 to 1.7 g / cm 2 .
[0018] In some embodiments of the present application, the compacted density P1 of the graphite material is 1.6 to 1.75 g / cm 2 .
[0019] In some embodiments of the present application, the compacted density P2 of the hard carbon material is 1.3-1.5 g / cm 2 .
[0020] In some embodiments of the present application, the compaction density P3 of the silicon-based material is 1 to 1.3 g / cm 2 .
[0021] In some embodiments of the present application, the porosity ε of the negative electrode sheet is 20 to 38%.
[0022] In some embodiments of the present application, the thickness H of the negative electrode active material layer is 25 to 60 μm.
[0023] In some embodiments of the present application, the mass fraction W1 of the graphite material in the negative electrode active material is 75-92%.
[0024] In some embodiments of the present application, the mass fraction W2 of the hard carbon material in the negative electrode active material is 3 to 10%.
[0025] In some embodiments of the present application, the mass fraction W3 of the silicon-based material in the negative electrode active material is 5 to 15%.
[0026] In some embodiments of the present application, the silicon-based material includes at least one of elemental silicon, silicon-oxygen compounds, and silicon alloys.
[0027] In some embodiments of the present application, the silicon-based material is further coated with a carbon layer on the surface of at least one of elemental silicon, silicon oxides, and silicon alloys.
[0028] In some embodiments of the present application, the coating amount of the carbon layer in the silicon-based material is 1 to 10 wt %, for example, it can be 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 wt %.
[0029] In some embodiments of the present application, the hard carbon material can be prepared by any preparation method known to those skilled in the art, including but not limited to a discharge plasma furnace preparation method using multiple fields such as Joule heat and high pressure, a starch / rice preparation method, a petroleum coke preparation method, a biomass preparation method, etc.
[0030] In some embodiments of the present application, the raw material of the negative electrode active material layer further includes at least one of a conductive agent and a binder. The conductive agent includes but is not limited to conductive graphite (such as KS-6, KS-15, SFG-6, SFG-15, SO, etc.), conductive carbon black (such as Super P, Super S, 350G, acetylene black, Ketjen black, etc.), conductive carbon fiber (such as VGCF, CNT) and graphene, etc. The binder includes but is not limited to at least one of polyvinylidene fluoride, polytetrafluoroethylene, carboxymethyl cellulose, styrene-butadiene rubber, polyurethane, polyvinyl alcohol, polyvinyl butyral, etc.
[0031] In some embodiments of the present application, the negative electrode active material layer includes 70 to 99 wt % of the negative electrode active material, 0.5 to 6 wt % of the conductive agent, and 0.5 to 20 wt % of the binder.
[0032] In some embodiments of the present application, when the negative electrode active material, the conductive agent and the binder are made into the negative electrode active material layer, the active material, the conductive agent and the binder are dispersed in a solvent and then coated on the negative electrode current collector, and dried to obtain the negative electrode active material layer.
[0033] The present application also relates to a method for preparing a negative electrode sheet, the method comprising the following steps:
[0034] The negative electrode active material slurry is coated on the negative electrode current collector to form a negative electrode sheet.
[0035] In some embodiments of the present application, the slurry of the negative electrode active material includes the negative electrode active material and at least one of a conductive agent and a binder. In some specific embodiments, the slurry of the negative electrode active material also includes a solvent.
[0036] In some embodiments of the present application, the method of coating the slurry of the negative electrode active material includes at least one of spraying, dipping, blade coating, transfer coating, extrusion coating, cast coating, micro-gravure coating, and the like.
[0037] According to a third aspect of the present application, a lithium-ion battery is provided. The lithium-ion battery comprises the aforementioned negative electrode sheet.
[0038] In some embodiments of the present application, the lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. The positive electrode sheet, the negative electrode sheet and the separator are wound, laminated or the like to obtain a battery cell and manufacture a lithium-ion battery.
[0039] In some embodiments of the present application, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer located on at least one side of the positive electrode current collector.
[0040] In some embodiments of the present application, the positive electrode current collector and the negative electrode current collector are independently selected from at least one of metal materials including metal foil (such as aluminum foil, silver foil, tin foil, iron foil, titanium foil, nickel foil, copper foil or alloy foil of the above metals), metal mesh (such as aluminum mesh, silver mesh, tin mesh, iron mesh, titanium mesh, nickel mesh, copper mesh or alloy mesh of the above metals).
[0041] In some embodiments of the present application, the positive electrode current collector is aluminum foil, and the negative electrode current collector is copper foil.
[0042] In some embodiments of the present application, the positive electrode active material layer includes a positive electrode active material, which is at least one of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium nickel manganese aluminum oxide.
[0043] In some embodiments of the present application, the raw material of the positive electrode active material layer also includes at least one of a conductive agent and a binder. The conductive agent includes but is not limited to conductive graphite (such as KS-6, KS-15, SFG-6, SFG-15, SO, etc.), conductive carbon black (such as Super P, Super S, 350G, acetylene black, Ketjen black, etc.), conductive carbon fiber (such as VGCF, CNT) and graphene, etc. The binder includes but is not limited to at least one of polyvinylidene fluoride, polytetrafluoroethylene, carboxymethyl cellulose, styrene-butadiene rubber, polyurethane, polyvinyl alcohol, polyvinyl butyral, etc.
[0044] In some embodiments of the present application, the positive electrode active material layer includes 70 to 99 wt % of the positive electrode active material, 0.5 to 6 wt % of the conductive agent, and 0.5 to 20 wt % of the binder.
[0045] In some embodiments of the present application, the electrolyte may be at least one of a solid electrolyte or an electrolyte.
[0046] In some embodiments of the present application, the electrolyte includes an electrolyte salt and an organic solvent, wherein the specific types and compositions of the electrolyte salt and the organic solvent are not subject to specific limitations.
[0047] In some embodiments of the present application, the electrolyte further includes additives, such as at least one of positive electrode film-forming additives, negative electrode film-forming additives, and cycle improving and low temperature additives.
[0048] In some embodiments of the present application, the separator comprises a polymer separator, and the polymer separator includes at least one of polyethylene, polypropylene, polyvinylidene fluoride, and multilayer composite films thereof.
[0049] In a fourth aspect of the present application, an electrical device is provided, the electrical device comprising the aforementioned lithium-ion battery.
[0050] Among them, electrical equipment refers to any equipment that can use electrical energy and convert it into mechanical energy, thermal energy, light energy or other one or more forms of energy, such as electric motors, electric heat engines, electric light sources, etc. Among them, mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc. Mobile devices can be mobile phones, laptops, drones, sweeping robots, electronic cigarettes, etc.; electric vehicles can be pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.
[0051] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. DETAILED DESCRIPTION
[0052] The following will clearly and completely describe the concept of the present application and the technical effects produced in combination with the embodiments, so as to fully understand the purpose, features and effects of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of them. Based on the embodiments of the present application, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present application.
[0053] The embodiments of the present application are described in detail below. The described embodiments are exemplary and are only used to explain the present application, and should not be understood as limiting the present application.
[0054] In the description of this application, "several" means more than one, "many" means more than two, "greater than", "less than", "exceed", etc. are understood to exclude the number itself, "above", "below", "within", etc. are understood to include the number itself, and "about" means within the range of ±20%, 10%, 8%, 5%, 4%, 3%, 2%, 1%, 0.5%, 0.2%, 0.1%, etc. of the number itself. If there is a description of "first" or "second", it is only used for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.
[0055] In the description of the present application, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0056] The present application is described below in conjunction with specific embodiments.
[0057] Examples 1 to 13
[0058] Embodiments 1 to 13 provide a negative electrode sheet and a lithium-ion battery comprising the negative electrode sheet, and the differences are as shown in Table 1, in the ratio between the negative electrode active materials, the particle size and Mohs hardness of the negative electrode active materials, the porosity of the negative electrode sheet, the thickness of the negative electrode active material layer, the compaction density of the negative electrode active material layer, the defect degree of the hard carbon material, the compaction rebound density, etc.
[0059] The preparation process of the negative electrode sheet is as follows:
[0060] Take the negative electrode active material (graphite material, hard carbon material, silicon-based material), conductive agent (conductive carbon black SP and carbon nanotube CNT mixed in a mass ratio of 9:1), and binder (styrene butadiene latex SBR and polyacrylate lithium PAALi mixed in a mass ratio of 0.5:1.8) in a mass ratio of 97.7:1.1:1.2 to prepare the negative electrode active material slurry, evenly apply it to the surfaces on both sides of the negative electrode current collector, and then cold press and strip to obtain the negative electrode sheet.
[0061] The preparation process of the positive electrode is as follows:
[0062] The positive electrode active material LiCoO2, the conductive agent acetylene black, the conductive carbon nanotubes, and the binder polyvinylidene fluoride PVDF are fully dispersed in an N-methylpyrrolidone NMP solvent system in a mass ratio of 97.6:0.5:0.6:1.3, evenly coated on the surfaces of both sides of the positive electrode current collector aluminum foil, and then dried and cut into positive electrode sheets.
[0063] Isolation film: The PE surface is coated with a ceramic mixture as an isolation film.
[0064] Electrolyte: Ethylene carbonate EC, propylene carbonate PC, diethyl carbonate DEC, and propyl propionate PP are mixed in a volume ratio of 1.2:1:4:4 to obtain a mixed organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent at a ratio of 1 mol / L to prepare an electrolyte.
[0065] Preparation of a full battery: The positive electrode sheet, separator, and negative electrode sheet are wound to produce a bare cell, which is then packaged and injected with electrolyte to produce a finished lithium-ion battery.
[0066] Table 1. Comparison of parameters of the examples and comparative examples
[0067]
[0068]
[0069] Comparative Examples 1 to 15
[0070] Comparative Examples 1 to 15 provide a negative electrode sheet and a lithium-ion battery respectively. The differences between Comparative Examples 1 to 15 and Examples 1 to 13 are shown in Table 1.
[0071] In the above embodiments and comparative examples:
[0072] The graphite material was purchased from Shanshan New Materials Co., Ltd. Examples 1 to 3, Examples 6 to 13, and Comparative Examples 1 to 15 used graphite material model DM-APG-0017-0002, Example 4 used graphite material model DM-APG-0020-0002, and Example 5 used graphite material model DM-APG-0027-0141.
[0073] The silicon-based materials were purchased from Jinsi Technology Co., Ltd. Examples 1 to 3, Example 6, Examples 8 to 13, and Comparative Examples 1 to 15 used silicon-based materials with model number YP-APS-0090-0000, Example 4 used silicon-based materials with model number YP-APS-0098-0000, Example 5 used silicon-based materials with model number YP-APS-0168-0000, and Example 7 used silicon-based materials with model number YP-APS-0054-0000, which are different porous carbon-coated silicon materials.
[0074] The preparation method of hard carbon material is as follows: 9.3g sucrose is dissolved in 100mL distilled water, poured into a Teflon hot pot and heated to 200℃, reacted at constant temperature for 6h, and the product is placed in a tubular furnace, heated to 1100℃ at a rate of 5℃ / min under an argon atmosphere, calcined and carbonized for 2h to obtain hard carbon. Among them, the carbonization heating rate is controlled to be 5, 2, and 1℃ / min, respectively, and hard carbon materials with different defect degrees can be obtained; by controlling the carbonization temperature to be 1100 and 1300℃, respectively, hard carbon materials with different hardness can be obtained.
[0075] The performance of the negative electrode sheets and lithium batteries of the embodiments and comparative examples were tested by the following methods:
[0076] (1) Energy density
[0077] Capacity calibration: 0.2C discharge to 3.0V; 0.5C constant current constant voltage charge to 4.5V, cut off 0.02C; then 0.2C discharge to 3.0V, record capacity C0 and energy W0; platform voltage V0 = W0 / C0.
[0078] The thickness of the battery in half-charged state was tested using 600PPG, and the length and width of the battery were measured using two-dimensional software.
[0079] The energy density is calculated according to the following formula: Energy density = [C0×V0 / (length×width×thickness)]×1000; wherein the respective units are as follows: platform voltage V0 (V), capacity C0 (mAh), energy W0 (mWh), length, width, thickness (mm).
[0080] (2) Cycle test
[0081] In an environment of 25℃, the cycle test was carried out according to the following method. Charging mode: 2.8C CC to 4.25V, 2C CC to4.35V, CV to 1.8C, 1.8C CC to 4.4V, CV to 1.5C, 1.5C CC to 4.5V, CV to 1.2C, 1.2CCC to 4.55V, CV to0.26C; Discharging mode: 0.7C DC to 3.0V.
[0082] 500-week capacity retention rate = discharge capacity at the 500th week / discharge capacity at the 1st week × 100%;
[0083] 500-week expansion rate = 500th-week full-charge thickness / initial half-charge thickness × 100%;
[0084] All battery thicknesses are tested using 600PPG.
[0085] (3) Fluid retention test
[0086] Fluid retention = fluid injection - fluid loss.
[0087] The results are shown in Table 2:
[0088] Table 2. Performance test results of the embodiments and comparative examples
[0089] Serial number Energy density (Wh / L) 500 weeks expansion rate (%) 500-week capacity retention rate (%) Liquid retention capacity (g) Example 1 800 11.99 85.64 7.31 Example 2 815 13.14 84.39 6.98 Example 3 790 10.79 86.75 6.65 Example 4 800 11.41 86.16 6.42 Example 5 800 11.68 85.99 7.49 Example 6 800 12.54 85.07 6.93 Example 7 800 11.90 85.77 6.96 Example 8 815 12.68 84.79 7.12 Example 9 828 13.24 84.02 7.39 Example 10 793 9.76 87.81 7.56 Embodiment 11 807 13.01 84.45 5.97 Example 12 804 11.57 86.05 7.01 Example 13 797 12.45 85.03 6.97 Comparative Example 1 792 20.11 75.56 6.03 Comparative Example 2 770 18.71 77.23 7.62 Comparative Example 3 760 9.03 89.88 6.34 Comparative Example 4 800 19.09 76.54 7.23 Comparative Example 5 800 18.88 77.26 7.19 Comparative Example 6 790 11.22 85.76 7.66 Comparative Example 7 810 17.97 78.34 5.78 Comparative Example 8 790 21.88 74.11 6.51 Comparative Example 9 800 20.65 75.31 6.37 Comparative Example 10 800 22.34 73.55 6.23 Comparative Example 11 800 21.22 74.33 6.87 Comparative Example 12 800 20.67 75.53 6.46 Comparative Example 13 800 20.89 75.19 6.76 Comparative Example 14 815 23.67 71.88 5.66 Comparative Example 15 780 17.23 79.03 7.13
[0090] Comparing Examples 1 to 3, as the ratio of the three negative electrode active materials changes, the porosity of the formed negative electrode sheet gradually decreases, the liquid retention amount gradually decreases, and the energy density and cycle performance also change accordingly. Comparing Examples 1, 4, and 5, graphite, hard carbon, and silicon-based materials with different particle sizes are used, and their porosity changes continuously, and the liquid retention amount, energy density, and cycle performance also change accordingly. Comparing Examples 2 to 4, the porosity of Example 4 is between Examples 2 and 3, and the three are relatively close, but because the silicon-based material has worse wettability for the electrolyte, and the content of silicon-based materials in Example 4 is higher, the liquid retention amount is lower than that of Example 3. Comparing Examples 7 to 9, as the coating thickness increases, the liquid retention amount gradually increases, but the cycle performance gradually decreases. Comparing Examples 12 to 13, as the defect degree of the hard carbon material increases, the energy density, cycle performance, and liquid retention amount gradually decrease.
[0091] Comparing Example 1 and Comparative Example 1, after the hard carbon material is omitted and replaced with graphite material, the porosity of Comparative Example 1 decreases significantly. Although the value of (kε+H) / P still meets the requirements, the liquid retention capacity is obviously attenuated, the energy density also decreases to a certain extent, and the expansion rate after 500 cycles is nearly doubled, and the capacity retention rate is also reduced by about 10%.
[0092] Comparing Example 1 and Comparative Example 2, after the silicon-based material is omitted and replaced with graphite material, the porosity of Comparative Example 2 increases, the liquid retention amount increases, but the energy density decreases significantly, the expansion rate after 500 cycles remains high, and the capacity retention rate also decreases significantly.
[0093] Comparing Example 1 and Comparative Example 3, Comparative Example 3 adopts a pure graphite system, and its expansion rate after 500 cycles is the lowest and its capacity retention rate is the highest, but its liquid retention amount and energy density are also at the lowest level.
[0094] Comparing Example 1 with Comparative Examples 4 to 5, the hard carbon defect I characterizes the degree of graphitization of the hard carbon material. The higher the degree of graphitization of the hard carbon, the more dependent the material is on interlayer lithium storage for lithium insertion. The specific surface area is lower and the pore structure is less. The volume expansion of the material during the cycle cannot be alleviated, which easily leads to carbon layer peeling. On the contrary, the hard carbon has low graphitization, more defect active sites, and a greater contribution to the capacity. An appropriate amount of defects can increase the reversible capacity. At the same time, the isotropy is better, which is conducive to the adsorption of lithium storage, weakens the volume expansion in the thickness direction, and is conducive to maintaining the stability of the cycle. Therefore, the defect degree of the hard carbon material in Comparative Examples 4 and 5 is too low or too high, and does not meet the defect degree requirements. The ratio of ordered structure and disordered structure in the hard carbon material is unbalanced, and the gain in battery cycle performance is greatly attenuated. The expansion rate and capacity retention rate of 500 cycles are at the level of Comparative Examples 1 or 2, which are significantly inferior to those of Example 1. However, the effect on liquid retention is small, and the liquid retention amount only decreases slightly.
[0095] Comparing Example 3 with Comparative Examples 6 to 7, in Comparative Examples 6 and 7, due to the compaction density P, porosity ε and thickness H of the negative electrode active material layer, (kε+H) / P is too low or too high, which makes it difficult for the electrolyte to infiltrate the negative electrode sheet under high pressure density, thereby limiting the improvement in the diffusion efficiency of the active ions.
[0096] Comparing Example 1 with Comparative Examples 8 to 9, the hardness of the silicon-based material in Comparative Example 8 is too low, and the hardness of the hard carbon material in Comparative Example 9 is too high. The particle hardness of the silicon-based material is greater than that of hard carbon and graphite, and it acts as a pulley during the rolling process of the negative electrode sheet, which can alleviate the locking caused by the angular shapes of hard carbon and graphite, facilitate the slippage between particles, and avoid local overpressure causing particle rupture. The hardness of silicon itself is relatively large, and reducing the hardness requires coating with a thicker carbon layer. The volume share of the carbon layer affects the energy density of the battery and also extends the path for lithium ions to be embedded in silicon. Excessive hardness of hard carbon will cause a physical short circuit inside the battery, which is most directly manifested as accelerated cycle attenuation. Therefore, the energy density and capacity retention rate in Comparative Examples 8 and 9 have declined compared to Example 1, while the thickness expansion rate has increased significantly.
[0097] Comparing Example 1 with Comparative Examples 10-13, the ratio of D50 / D′50 in Comparative Examples 10-11 is too large or too small, and the ratio of D′50 / D″50 in Comparative Examples 12-13 is too low or too high. Under the same compaction density, the particles squeeze each other, which seriously affects the structural stability of the material itself, and the porosity of the pole piece is low, resulting in unsatisfactory liquid retention effect. For example, in Comparative Examples 10-11, the graphite particle size is too large, and the silicon-based material and the hard carbon material are densely distributed in the gap between the graphites; the hard carbon material particle size is too large, and the gap formed by the hard carbon and the graphite is enlarged, and a large amount of silicon-based material is concentrated and distributed in the gap between the two. , the volume expansion of silicon-based materials caused during the working process cannot be alleviated. Therefore, the 500-week thickness expansion rate of the two comparison examples is even higher than that of comparison example 1, and the capacity retention rate is lower than that of comparison example 1. In comparison examples 12 to 13, when the particle size of the silicon-based material is too large, it is difficult to embed into the gaps between hard carbon and graphite; if the hard carbon is too large, the silicon-based material cannot be well retained in the gaps between hard carbon and graphite. In Example 1, silicon-based materials with appropriate particle sizes are distributed between the gaps between hard carbon and graphite, which not only increases the compaction density of the pole piece, but also further limits the volume expansion that occurs during the lithium insertion process, thereby improving the cycle performance of the battery.
[0098] Comparing Example 4 with Comparative Examples 14 and 15, the porosity in Comparative Examples 14 to 15 is low and the compaction density of the negative electrode sheet is too high or too low. Although Formula 1 is still satisfied, a certain degree of decrease occurs in one or more aspects such as energy density, cycle capacity retention rate, expansion rate and liquid retention amount, and some performance is lower than that of Comparative Examples 1 to 3.
[0099] Therefore, based on the above embodiments and comparative examples 1 to 15: the lithium-ion battery using the negative electrode provided in the embodiments of the present application still has a good capacity retention rate and a low battery expansion rate after long-term cycle charge and discharge, which is significantly better than comparative examples 1 to 2; compared with the pure graphite system of comparative example 3, the energy density of the battery has also been greatly improved, which can better meet the market demand, and the good porosity enhances the infiltration of the electrolyte, providing a guarantee for the long-cycle stability of the battery. Therefore, the negative electrode provided in the embodiments of the present application can significantly improve the cycle performance of the lithium-ion battery, solve the problem of battery failure caused by large material expansion, and the battery cell also has good liquid retention and high energy density.
[0100] The present application is described in detail above in conjunction with the embodiments, but the present application is not limited to the above embodiments, and various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present application. In addition, the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.
Claims
1. A negative electrode sheet, characterized in that: The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode active material, and the negative electrode active material comprises a graphite material, a hard carbon material and a silicon-based material; The particle size D50 of the graphite material, the particle size D′50 of the hard carbon material, and the particle size D″50 of the silicon-based material satisfy 1.5≤D50 / D′50≤2.5, and 1.1≤D′50 / D″50≤3.
2. The negative electrode sheet according to claim 1, characterized in that: D50 is 10 to 17 μm, D′50 is 6 to 10 μm, and D″50 is 3 to 7 μm.
3. The negative electrode sheet according to claim 1, characterized in that: The defect degree I of the hard carbon material is 0.15 to 0.38; Wherein, I is the peak area A of G when the hard carbon material is subjected to Raman spectrum test G and D peak area A D ratio.
4. The negative electrode sheet according to claim 1, characterized in that: The Mohs hardness S1 of the graphite material is 0.8-2, the Mohs hardness S2 of the hard carbon material is 3-5, the Mohs hardness S3 of the silicon-based material is 5-7, and S2 <S3。 5. The negative electrode sheet according to claim 1, characterized in that: The compaction density P, the porosity ε of the negative electrode sheet and the thickness H of the negative electrode active material layer satisfy Formula 1: 15≤(kε+H) / P≤39.05; In formula 1: 1.26≤k≤1.40, P is g / cm 2 The unit of α is the dimensionless value for calculation, and the unit of H is μm for calculation.
6. The negative electrode sheet according to claim 5, characterized in that: The compaction density P of the negative electrode sheet is 1.55-1.7 g / cm 2 The compacted density P1 of the graphite material is 1.6 to 1.75 g / cm 2 The compaction density P2 of the hard carbon material is 1.3 to 1.5 g / cm 2 The compaction density P3 of the silicon-based material is 1 to 1.3 g / cm 2 .
7. The negative electrode sheet according to claim 5, characterized in that: The porosity ε of the negative electrode sheet is 20-38%, and the thickness H of the negative electrode active material layer is 25-60 μm.
8. The negative electrode sheet according to claim 1, characterized in that: The mass fraction W1 of the graphite material in the negative electrode active material is 75-92%, the mass fraction W2 of the hard carbon material in the negative electrode active material is 3-10%, and the mass fraction W3 of the silicon-based material in the negative electrode active material is 5-15%.
9. A lithium-ion battery, characterized in that A negative electrode sheet comprising any one of claims 1 to 8.
10. Electrical equipment, characterized in that: Includes the lithium ion battery as claimed in claim 9.
Citation Information
Patent Citations
Method for preparing compactly coated silicon-carbon nanocomposite
CN109873132A
Negative pole piece as well as preparation method and application thereof
CN116581271A
Secondary battery, battery module, battery pack, and electric device
CN116888759A
Silicon-based graphite composite material and preparation method and application thereof
CN117239082A
Carbon silicon based negative electrode active material for lithium ion secondary batteries, and method for manufacturing the same
JP2015207428A
Cited By
High-energy-density fast-charging lithium ion battery
CN121416579A
Electrochemical apparatus and electronic device
WO2026199232A1